Streamlining the Foreign Trade Policy of the Republic of Moldova - T. G. Gutium (Informaciâ i Innovacii, 2021)
The Republic of Moldova faced two shocks in 2020: the drought, which led to a decrease in crop production by more than a third, and the spread of the virus that causes severe acute respiratory syndrome (SARSCoV-2), which led to lockdowns, temporary suspension of the activities of enterprises and organizations. In this situation, the main task facing the state is sustainable economic growth. Thus, the improvement of foreign trade policy is relevant, since the development of economic relations with other countries, an increase in the export potential of the national economy will ensure stable economic growth. The primary goal of this study is to improve the foreign trade policy of the Republic of Moldova. The main methods used are statistical research method, a systematic approach, an abstract-logical research method, etc. As a result of the study, the main and specific objectives were developed that need to be included in government programs and strategies aimed at promoting exports, developing trade and economic relationship.